Facility for Separation of Fine-Dispersed Raw Iron Ore by Combined Effect of Permanent and Variable Magnetic Fields - Ponomarenko, O.M.; Brik, O.B.; Dudchenko, N.O.; Yevtekhov, V.D. (Science and Innovation, 2024)
An analogue of semi-industrial facility for the separation of finely dispersed raw iron ore has been created. Using the created facility, magnetic separation of raw iron ore samples from the tailing dump of Valyavko «Severnaya» mine concentrator has been carried out. The samples have been separated after transformation of hematite to magnetite using carbon monoxide. It has been shown by X-ray diffraction method that the initial transformed ore was mainly represented by magnetite and quartz, and the concentrate — by magnetite. Reflexes on the diffractogram of tailings obtained by magnetic separation have shown that the tailings mainly consist of quartz. The iron content in iron-ore concentrate was 69.5 w/w%.